Effect of Counterion on the Solvatochromic Properties of Heteroleptic Chelate Copper(II) Complexes - Hamid Golchoubian; Hakimeh Fazilati (Journal of Spectroscopy)
A series of heteroleptic chelate copper(II) complexes of the type [Cu(L)(acac)]X where acac = acetylacetonate; L = N,N′-1,6-bis(2-fluorophenyl)-2,5-diazahexane; X=CIO4-, BPh4-, PF6-, and BF4- have been prepared and characterized by elemental analyses, IR and UV-Vis spectroscopies, and molar conductance measurements. The prepared complexes are fairly soluble in a large number of organic solvents and show positive solvatochromism. Among the complexes [Cu(L)(acac)]ClO4, it is demonstrated the most solvatochromism. A multiparametric equation has been utilized to explain the solvent effect on the d-d transition of the complexes using SPSS/PC software. To explore the mechanism of interaction between solvent molecules and the complexes, different solvent parameters such as DN, AN, α, ET(30), π*, and β using stepwise multiple linear regression (SMLR) method were employed. The results demonstrated that the donor power of the solvent plays the most important role in the solvatochromism of the compounds.